Conversations in postcolonial thought - Sian, Katy P., 1984- (Palgrave Macmillan, 2014)
"Based on original material, this book offers a series of 12 conversational interviews with a diverse set of postcolonial thinkers from across the globe in the social sciences and humanities. Using a biographical approach to map out life histories, uniquely this book not only examines the key ideas of the thinkers interviewed, but it also invites readers to share their personal journeys to help one understand the experiences that led to their work within the field. The selection of thinkers included within this text is done so not with the aim to offer an encyclopedic index, but rather, to show how postcolonial thought as a broader concern can been found across a range of disciplines"--